2011
DOI: 10.1186/1824-7288-37-55
|View full text |Cite
|
Sign up to set email alerts
|

Meconium obstruction in absence of cystic fibrosis in low birth weight infants: an emerging challenge from increasing survival

Abstract: BackgroundMeconium abnormalities are characterized by a wide spectrum of severity, from the meconium plug syndrome to the complicated meconium ileus associated with cystic fibrosis. Meconium Related Ileus in absence of Cystic Fibrosis includes a combination of highly viscid meconium and poor intestinal motility, low grade obstruction, benign systemic and abdominal examination, distended loops without air fluid levels. Associated risk factors are severe prematurity and low birth weight, Caesarean delivery, Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…The viscoid meconium and poor intestinal mobility cause a blocked ileum in 10--20% of individuals with CF and may require surgical intervention (21). As the individual with CF gets older, viscid fecal material may continue to potentially obstruct the terminal ileus and proximal colon in a condition known as distal intestinal obstruction syndrome (DIOS).…”
Section: Age and Sex Characteristicsmentioning
confidence: 99%
“…The viscoid meconium and poor intestinal mobility cause a blocked ileum in 10--20% of individuals with CF and may require surgical intervention (21). As the individual with CF gets older, viscid fecal material may continue to potentially obstruct the terminal ileus and proximal colon in a condition known as distal intestinal obstruction syndrome (DIOS).…”
Section: Age and Sex Characteristicsmentioning
confidence: 99%
“…88,89 Sometimes, intestinal obstruction may be due to the meconium ileus with cystic fibrosis as the underlying pathology. 90,91 Diagnosis of anorectal malformations is usually done in late pregnancy or in the early neonatal period. Timing of diagnosis does not interfere with typical treatment of these malformations.…”
Section: Duodenal Atresia and Jejunoileal Atresiamentioning
confidence: 99%
“…Cases of MI in which additional bowel abnormalities such as atresia, volvulus, or perforation have arisen are here described as “complicated MI” (see Figure ). While once thought to be almost pathognomonic of CF, recent studies have demonstrated the surprisingly high prevalence of MI without positive CF testing . For the subset of patients with complicated MI, the relationship to CF becomes even less clear as the incidence of complications arising from MI may be even higher in patients without CF …”
Section: Introductionmentioning
confidence: 99%
“…While once thought to be almost pathognomonic of CF, recent studies have demonstrated the surprisingly high prevalence of MI without positive CF testing. [2][3][4][5] For the subset of patients with complicated MI, the relationship to CF becomes even less clear as the incidence of complications arising from MI may be even higher in patients without CF. 3 In either population, the accurate distinction between isolated and complicated MI is critical in determining the prognosis, degree of intervention, and most appropriate timing of treatment.…”
Section: Introductionmentioning
confidence: 99%